Corrosion behavior of Zn-incorporated antibacterial TiO2 porous coating on titanium - Zhang, Xiangyu; Wang, Huizhen; Li, Jiangfang; He, Xiaojing; Hang, Ruiqiang; Huang, Xiaobo; Tian, Linhai; Tang, Bin (Ceramics international, 2016)
Incorporation of antibacterial agents (e.g. Ag and Cu) at the surface of biomedical materials has evolved as a potentially effective method for preventing the bacterial infections. However, the antibacterial efficacy of medical device implants must necessarily be balanced by good corrosion resistance and the corrosion behavior of the antibacterial coatings has seldom been reported. In this work, Zn-incorporated antibacterial TiO2 coating was produced on pure titanium (Ti) by micro-arc oxidization (MAO) and the electrochemical behavior was assessed. The results obtained from the antibacterial studies suggest that the Zn-incorporated TiO2 coating provides bactericidal activity against both Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus) over 90%. The corrosion behavior of Zn-incorporated TiO2 coating were investigated using a combination of complementary electrochemical measurement techniques such as open circuit potential (OCP), potentiodynamic polarization and electrochemical impedance spectroscopy. The results show that the Zn-incorporated TiO2 coating move the OCP to the positive direction and increase the polarization resistance, thereby enhances the corrosion resistance of pure Ti. Collectively, the Zn-incorporated TiO2 coating with both antibacterial ability and anti-corrosive properties might be more suitable for biomedical surfaces.